The role and place of ethnopedagogy in the educational ecosystem - Tatyana Vasilievna Tretyakova (Universidade Estadual Paulista, 2021)
This article addresses various educational systems that have led to the transition to the educational ecosystem. Application of ethno-pedagogical bases in the modern innovative educational process expands frontiers of knowledge on the way of comprehension of this environment, provides the formation of ecological consciousness and forms world outlook structures, a priori providing coevolution of the person and society, the individual and nature, the person and the world. The process of transition from the educational environment to the educational ecosystem, focuses on learning throughout a lifetime and continuous professional development, adapting the person to the new challenges of our time. The relevance of the transition is due to the progressive development of the human community, which tirelessly modernizes the essence and place of the educational system in the sociocultural environment. Not the lowest of the roles should be given to traditional folk pedagogical methods, mechanisms, and ways of education and training.